(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In contemporary world literature, issues of cultural encoding/decoding, heritage, mythopoetic modeling, and ultimately the creation of a new aesthetic paradigm are being reactualized. This problematic is objectively correlated with the theoretical and critical understanding of the content and functional orientation of cultural codes inherent to any national literature to varying degrees. The significance of developing the theory of cultural code in the context of literature and art on a national and international scale, beyond its scientific value and novelty, is determined by several interdisciplinary and social factors.